Inca’s Fiscal Regime - D'Altroy, Terence (2018)
The present article is intended to describe the Inkas’ state economy in a comparative conceptual framework, while explaining how their own view of things directed the economy’s trajectory. Although other authors have made similar efforts, most prominently from Marxist perspectives, investigators working in the Andes generally work with terminology that is distinctly Andean in content and grounded in economic anthropology (see below). Most of this chapter is devoted to describing the state economy, but it will be useful at the inception to ask how applicable the Eurocentric frameworks described in this volume’s introduction are to the premodern American cases. The analytical vocabularies employed for European fiscal history, such as “fiscal state,” “domain state,” or “fiscal regime,” are seldom if ever applied. This situation does not necessarily imply that such concepts are not translatable to the Inka Empire, but it does require that we assess the utility of their application